Application of coal waste in sustainable roller compacted concrete pavement-environmental and technical assessment. Issue Volume 19:Issued 8(2018) (3rd August 2018) - Modarres, Amir; Hesami, Saeid; Soltaninejad, Mostafa; Madani, Hesam
Abstract: To minimise the adverse environmental impacts of coal mining wastes, utilising coal waste in various applications such as sustainable concrete pavements could be explored. This research investigates the effects of using coal waste and its ignited product in roller compacted concrete pavement (RCCP). The combination of limestone powder (LS) and coal waste ash (CWA) was also studied. The main laboratory programme consisted of pozzolanic reactivity determination, compressive strength test, toughness test, toxicity characteristic leaching procedure (TCLP) test, setting times and microstructure analysis. The results indicated that compared to the binary mixes, the use of LS as a complement of CWA enhanced the mechanical properties, including compressive strength and toughness, especially at higher replacement levels and later ages. TCLP test results revealed that the RCCP mixtures had heavy metals with lower concentration than the standard levels indicated in US environmental protection agency. The microstructural investigations also showed that a denser microstructure could be obtained by using CWA as a partial replacement of cement, especially in combination with limestone. It could be concluded that the use of coal waste powder and its ash reduces the volume of hazardous waste in nature and is regarded as a step towards sustainability.